2003
DOI: 10.1115/1.1527904
|View full text |Cite
|
Sign up to set email alerts
|

Nusselt Number Behavior on Deep Dimpled Surfaces Within a Channel

Abstract: Experimental results, measured on a dimpled test surface placed on one wall of a channel, are given for a ratio of air inlet stagnation temperature to surface temperature of approximately 0.94, and Reynolds numbers R eH from 12,000 to 70,000. These data include friction factors, local Nusselt numbers, spatially-resolved local Nusselt numbers, and globally-averaged Nusselt numbers. The ratio of dimple depth to dimple print diameterand the ratio of channel height to dimple print diameter is 1.00. These results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(17 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…When Reynolds number increased from 12000 to 70000, the friction factor ratio also increased from 1.6 to 2.6. Silva et al [80] and Burgess et al [81] opined that the use of dimples increased pressure drop and these results are contradictory to that reported by Kim et al [79].…”
Section: Dimplesmentioning
confidence: 78%
See 1 more Smart Citation
“…When Reynolds number increased from 12000 to 70000, the friction factor ratio also increased from 1.6 to 2.6. Silva et al [80] and Burgess et al [81] opined that the use of dimples increased pressure drop and these results are contradictory to that reported by Kim et al [79].…”
Section: Dimplesmentioning
confidence: 78%
“…Hence, the uses of dimples are suggested only for laminar flow application such as in microelectronic cooling. In addition, Burgess et al [81] found experimentally that dimples enhanced heat transfer performance; however, friction factor ratios increased with the increasing Reynolds number. When Reynolds number increased from 12000 to 70000, the friction factor ratio also increased from 1.6 to 2.6.…”
Section: Dimplesmentioning
confidence: 96%
“…This is also supported by Refs. [6,7,11]. Moon et al [11] have concluded that the normalized Nusselt number is not a function of Reynolds number, and the friction factor is relatively independent of Reynolds number.…”
Section: Resultsmentioning
confidence: 97%
“…Mahmood et al [5] have presented heat transfer characteristics when dimples and protrusions are placed on opposite walls. Experimental study of staggered arrays of dimples on a single surface has been reported by Burgess and Ligrani [6] and Burgess et al [7]. Seven different dimple depressions on the surface have been studied by Park and Ligrani [8].…”
Section: Introductionmentioning
confidence: 95%
“…Mahmood et al [9] describe the mechanisms responsible for local and spatially-averaged heat transfer augmentations on flat channel surfaces with an array of dimples on one wall for one channel height equal to 50 percent of the dimple print diameter. Other recent investigations consider flow and heat transfer in single spherical cavities [10], effects of dimples and protrusions on opposite channel walls [11,12], the effects of dimple depth on vortex structure and surface heat transfer [13,14], the effects of deep dimples on local surface Nusselt number distributions [15], the combined influences of aspect ratio, temperature ratio, Reynolds number, and flow structure [16], and the flow structure due to dimple depressions on a channel surface [17].…”
Section: Dimpled Test Surfacementioning
confidence: 99%